TOPOLOGY OF AN AMPHIPHILIC MITOCHONDRIAL SIGNAL SEQUENCE IN THE MEMBRANE-INSERTED STATE - A SPIN-LABELING STUDY - YU, YG; THORGEIRSSON, TE; SHIN, YK (AMER CHEMICAL SOC, 1994)
To investigate the interaction of the presequence of the precursor of yeast cytochrome C oxidase subunit IV (COX IV) with phospholipid membranes, a series of single- and double-cysteine-substituted peptide variants derived from the 25-residue NH2-terminal presequence has been synthesized and modified with nitroxide spin labels. The immersion depth, orientation, and secondary structure of the peptide in the POPC bilayer containing 10 mol % POPG were determined using electron paramagnetic resonance (EPR) spectroscopy. EPR saturation analysis of singly labeled variants reveals that the nitroxides attached to the NH2-terminal region of the peptide insert into the acyl chain region of the bilayer, approximately 13 Angstrom deep from the membrane surface. EPR line shape analysis of doubly labeled variants indicates that the peptide predominantly exists as an extended conformation, with little secondary structure. The experimental results, together with the energetic consideration of peptide-bilayer interactions, suggest that the presequence is located near the interface between the head group region and the acyl chain region, such that the hydrophobic side chains are solvated by the acyl chains and the charged side chains extended toward the polar environment at the bilayer surface.
Keywords: PHASE PEPTIDE-SYNTHESIS; INNER MEMBRANE; IMPORT; PROTEINS; PRESEQUENCE; CONFORMATION; RESONANCE; VESICLES; MUTANTS; HELICES